2022
DOI: 10.1007/s00520-022-07344-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of adherence to pelvic floor muscle exercises and vaginal dilator use among gynecologic cancer patients: a qualitative study

Abstract: Objective Women with gynecologic cancer may suffer from pelvic floor dysfunction (PFD). Before radiotherapy, prehabilitation with pelvic floor muscle exercises (PFME) and vaginal dilator (VD) might prevent it and foster sexual life. This study aims to explore the experience of gynecologic cancer patients getting external beam radiation treatments regarding barriers to and facilitators of adherence to a prehabilitation program to prevent PFD. Methods This qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…(Cooper et al., 2022)
Well, you're always opening WhatsApp, so the first thing I saw was the WhatsApp which I had named ‘Physio’, so I listened to the exercises and it really helped! (Araya‐Castro et al., 2022)
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Cooper et al., 2022)
Well, you're always opening WhatsApp, so the first thing I saw was the WhatsApp which I had named ‘Physio’, so I listened to the exercises and it really helped! (Araya‐Castro et al., 2022)
…”
Section: Resultsmentioning
confidence: 99%
“…Our relationship got stronger and that's good. (Araya-Castro et al, 2022) Theme 4: Physical opportunities (124/660, 19%)…”
Section: Psychological Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research conducted in a gynecological setting identified serious barriers to implementing PFR, including misinformation, lack of coordination with the treatment team, and feelings of shame [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of therapy, feedback from the attending physician about the effect of treatment on a functional level, psychosocial development, and expectations for future improvements does not always reach the referring parties. Previous research shows that such feedback is an enabler when present or a barrier when absent [ 21 ].…”
Section: Discussionmentioning
confidence: 99%